INTELLECTUAL CAPITAL : PENDEFINISIAN, PENGAKUAN, PENGUKURAN, PELAPORAN DAN PENGUNGKAPAN - Sudarno Sudarno; Nourma Yulia (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
A paradigm shift of labour based business to knowledge based business has an impact on financial reporting. There are other things that are necessarily stated to financial report users which can explain value-added the company has such as innovation, findings, knowledge and skills of human resources, relations with consumers, etc. most frequently known as intellectual capital. The company’s inability to record intangible asset in the balance is because the current accounting standard has not yet been able to capture and report undertaken investment in order to gain non-physical resources. This research was conducted by qualitative approach (literature study) which explained the concept of intellectual capital from definition, recognition, measurement, reporting and disclosure. Keywords: Intellectual Capital, Definition, Recognition, Measurement, Reporting and Disclosure.